PENTINGNYA PENDEKATAN PEDAGOGI DALAM MENYIAPKAN LULUSAN SMK YANG SIAP KERJA DI SMK NEGERI 9 BENGKULU UTARA - Robiyani; Adi Asmara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
competencies to prepare them for entering the workforce, continuing their education, or becoming entrepreneurs. To achieve these goals, an appropriate pedagogical approach is required so that the learning process focuses not only on mastering theory but also on developing students' skills, character, and professional attitudes. An effective pedagogical approach can create active, creative, innovative, and student-centered learning. This article discusses the importance of a pedagogical approach in preparing work-ready vocational high school graduates, its implementation strategies, challenges faced, and efforts to improve the quality of learning at SMK Negeri 9 North Bengkulu. The research method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results show that the implementation of innovative learning models such as Project-Based Learning (PjBL), Teaching Factory, and Field Work Practice (PKL), supported by teachers' pedagogical competence, significantly improves students' work readiness.